Incoterms 2000 - Sherlock, Jim (Henry Stewart Talks, 2009)
The origins of Incoterms 2000, Their importance in international trade contracts, Defining the costs, Defining the delivery obligations, Defining the point where risk passes, EEX to DDP, FOB and CIF problems with the 'ship's rail', Introduction of FCA and CIP, The most appropriate terms